Praktik Pendidikan Generasi Qur’ani Era Milenial di Rumah Qur’an Al-Falah Galang - Ameilia Cindy; Mahariah Mahariah (At Turots: Jurnal Pendidikan Islam, 2023)
In the midst of everyday life, parents have found a lot of concern about the quality of their children's emotional, intellectual and spiritual intelligence. For example, there is a gap between parents who expect Qur'anic characteristics for their children at school, but in reality schools are not able to accommodate parents' expectations. It is possible that schools are not only places where Al-Qur'an lessons are taught, so that the portion of expectations is sometimes not fulfilled, the number of students is large. not compared by the teacher to accommodate. In the social environment, children in the millennial era are often very far from the Qur'anic character, this is the cause of children following negative environmental currents. The purpose of this research focuses on the implementation of orientations, programs and learning outcomes in shaping the Qur'anic generation in the millennial era. This research was conducted at Al-Falah Galang Qur'an House, Environment II, Galang City, Kec. Poor. This study uses a type of qualitative research with a phenomenological approach. The data sources in this study are the founders, teachers, students and parents. Data collection techniques using observation, interviews, and documentation studies. Studies have shown that the learning program at the Al-Falah Galang Qur’an House be optimally, supported by the orientation and the attainment of learning by teachers.